(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
In this article, taking into account the hot and dry climatic conditions of the Central Asian region, huge construction facilities are being built in the desert regions of Kyzylqum, Karakum and mountainous districts. and monitoring the health of builders in constructions is important.